JENIS JENIS PERBUATAN CURANG YANG MERUGIKAN HAK KONSUMEN DALAM UNDANG UNDANG PERLINDUNGAN KONSUMEN - Herry Anto Simanjuntak (Universitas Quality, 2020)
In the business world, there are often fraudulent acts that can harm consumers due to the behavior of business actors who do not heed business rules and ethics that justify any unhealthy means. Because of this fraudulent act, Law Number 8 of 1999 concerning Consumer Protection or also known as UUPK was born to minimize fraudulent acts as much as possible which is regulated in detail in Chapter IV concerning Prohibited Acts for business actors starting from the provisions of Article 8 to Article 18. UUPK. However, even though there are regulations that prohibit prohibiting actions, it is not the intention of business actors that appear in the community that are reported either through print or electronic media. The issue of consumer protection is not an individual problem, but is actually a common problem and a national problem because in one respondent everyone is a consumer, therefore protecting consumers is protecting everyone. Consumer protection is not only about finding who is responsible and what the law is, but also about education for consumers and awareness of all parties about the safety and security of all parties in consuming their needs. With the issuance of the Consumer Protection Law (Law No.8 of 1999) there is nothing to kill the business of business actors, but instead encourages a healthy business climate and encourages the birth of companies that are tough in facing existing competition by providing quality goods / services. In the general explanation of the UUPK why its implementation will still take into account the rights and actors of small and medium enterprises. The responsibility of business actors for fraudulent acts that harm the rights of consumers is the absolute responsibility of business actors to provide compensation for damage, pollution, and consumer losses due to consuming goods or services produced or taken over. There are times when business actors are not willing to take responsibility, so consumers can sue through the Consumer Dispute Resolution Agency (BPSK) or to the District Court so that the business actor is given administrative or criminal or civil penalties.